THE EFFECT OF DIETARY VITAMIN E AND ZINC LEVELS ON PERFORMANCE AND LIPID OXIDATION IN FRESH AND STORED EGGS OF LAYING DUCKS - Arif Darmawan; Sumiati Sumiati; Widya Hermana (Faculty of Animal Science, Universitas Gadjah Mada, 2017)
Vitamin E and zinc are necessary for preventing free radical damage to phospholipid membranes, enzymes and other important molecules. The objective of this study was to evaluate the effect of dietary vitamin E and zinc levels on performance and lipid oxidation in fresh and stored eggs of laying duck. A total of 90 of 22 weeks old ducks were randomly divided into 15 experimental units by assigning a completely randomized design with 5 treatments and 3 replications. The treatment diets were R1 (control diet), R2 (R1+40 IU vitamin E), R3 (R1+80 IU vitamin E), R4 (R1+100 ppm organic zinc), and R5 (R1+200 ppm organic zinc).The experiment was carried out for 8 wk. Parameters observed were feed intake, egg production, egg weight, feed conversion ratio, and Thiobarbituric Acid Reactive Substances (TBARS) value. The results showed that increasing of vitamin E from 40 IU to 80 IU and zinc from 100 ppm to 200 ppm did not affect feed intake and egg weight. Otherwise, the dietary Vitamin E and organic zinc significantly decreased (P<0.05) feed conversion ratio and significantly increased (P<0.05) egg production and decreased (P<0.01) TBARS values. It is concluded that dietary 40 IU vitamin E or 100 ppm organic zinc could increase the performance of laying ducks and dietary 200 ppm organic zinc was more efective to be antioxidant than 40 and 80 IU vitamin E.